Identification of some Bioactive Metabolites in a Fractionated Methanol Extract from Ipomoea aquatica (Aerial Parts) through TLC, HPLC, UPLC‐ESI‐QTOF‐MS and LC‐SPE‐NMR Fingerprints Analyses. Issue 1 (4th August 2017) - Hefny Gad, Mahmoud; Tuenter, Emmy; El‐Sawi, Nagwa; Younes, Sabry; El‐Ghadban, El‐Mewafy; Demeyer, Kristiaan; Pieters, Luc; Vander Heyden, Yvan; Mangelings, Debby
Abstract: Introduction: The plant species Ipomoea aquatica contains various bioactive constituents, e.g. phenols and flavonoids, which have several medical uses. All previous studies were executed in Asia; however, no reports are available from Africa, and the secondary metabolites of this plant species from Africa are still unknown. Objective: The present study aims finding suitable conditions to identify the bioactive compounds from different fractions. Methodology: Chromatographic fingerprint profiles of different fractions were developed using high‐performance liquid chromatography (HPLC) and then these conditions were transferred to thin‐layer chromatography (TLC). Subsequently, the chemical structure of some bioactive compounds was elucidated using ultra‐performance liquid chromatography‐quadrupole time of flight‐tandem mass spectrometry (UPLC‐QTOF‐MS) and liquid chromatography‐solid phase extraction‐nuclear magnetic resonance (LC‐SPE‐NMR) spectroscopy. Results: The HPLC fingerprints, developed on two coupled Chromolith RP‐18e columns, using a gradient mobile phase (methanol/water/trifluoroacetic acid, 5:95:0.05, v / v / v ), showed more peaks than the TLC profile. The TLC fingerprint allows the identification of the types of chemical constituents, e.g. flavonoids. Two flavonoids (nicotiflorin and ramnazin‐3‐O‐rutinoside) and two phenolic compounds (dihydroxybenzoic acid pentoside and di‐pentoside) were tentatively identified by QTOF‐MS, while NMR confirmed the structure of rutin and nicotiflorin. Conclusion: The HPLC and TLC results showed that HPLC fingerprints give more and better separated peaks, but TLC helped in determining the class of the active compounds in some fractions. Bioactive constituents were identified as well using MS and NMR analyses. Two flavonoids and two phenolic compounds were tentatively identified in this species for the first time, to the best of our knowledge. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : ‐ Comparison of information from HPLC and HPTLC fingerprints of different Ipomoea aquatica fractions. ‐ Tentative identification of eight compounds in ethyl acetate‐methanol fraction using UPLC‐QTOF‐MS. ‐ Confirmation the chemical structure of rutin and nicotiflorin using LC‐SPE‐NMR.